2023
DOI: 10.2478/cjf-2023-0005
|View full text |Cite
|
Sign up to set email alerts
|

Decline of Artisanal Fisheries in the Croatian Section of the Sava River

Abstract: The aim of this research is to analyse the trends of the total artisanal fish catch in the Croatian section of the Sava River. All 17 years of the study (2004-2020) showed a negative trend that became highly statistically significant (p<0.01) in the last eight years. In addition to the total catch, the catch per unit effort (CPUE) also decreased significantly (p<0.05) throughout the study. The reasons for these negative trends are discussed, including a possible decline in artisanal interest, higher fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In the same period, the catches of the other three species mentioned in the register, starlet Acipenser ruthenus, asp Leuciscus aspius and tench Tinca tinca, fluctuated without trend, which can be attributed to high CV at the low quantities (Treer, 2022). These negative trends in absolute catch numbers (kg) are followed by a significant decline in CPUE (P < 0.01) among artisanal fishers (Treer, 2023). The decline in catches of sought-after fish species can also be observed elsewhere and has been thoroughly investigated in the Baltic Sea, where declines have been recorded particularly for pike (Nilsson et al, 2019;Bergström et al, 2022;Psuty et al, 2023), pike perch and roach Rutilus rutilus (Mustamaki et al, 2014;Andrasunas et al, 2022).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…In the same period, the catches of the other three species mentioned in the register, starlet Acipenser ruthenus, asp Leuciscus aspius and tench Tinca tinca, fluctuated without trend, which can be attributed to high CV at the low quantities (Treer, 2022). These negative trends in absolute catch numbers (kg) are followed by a significant decline in CPUE (P < 0.01) among artisanal fishers (Treer, 2023). The decline in catches of sought-after fish species can also be observed elsewhere and has been thoroughly investigated in the Baltic Sea, where declines have been recorded particularly for pike (Nilsson et al, 2019;Bergström et al, 2022;Psuty et al, 2023), pike perch and roach Rutilus rutilus (Mustamaki et al, 2014;Andrasunas et al, 2022).…”
Section: Resultsmentioning
confidence: 88%
“…Its lower part flows along the border with Bosnia and Herzegovina, where both fishing activities are allowed in both countries -artisanal fishing and recreational fishing (angling). Previous studies have shown that total commercial catches have declined sharply in the Croatian section (Treer, 2023). In addition, the last part of the river in Croatia (Vukovar-Sirmiun County) is characterised by the trend of declining catches of common carp Cyprinus carpio, northern pike Esox lucius, pike perch Sander lucioperca and wels catfish Silurus glanis (Treer, 2022).…”
Section: Introductionmentioning
confidence: 99%